2017
DOI: 10.1007/s10620-017-4710-z
|View full text |Cite
|
Sign up to set email alerts
|

NF-E2-Related Factor 2 Suppresses Intestinal Fibrosis by Inhibiting Reactive Oxygen Species-Dependent TGF-β1/SMADs Pathway

Abstract: The results suggested that Nrf2 suppressed intestinal fibrosis by inhibiting ROS/TGF-β1/SMADs pathway in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…CIN is also known to be a potent antioxidant phytochemical that activates the antioxidant NRF2/HMOX1 and NQO1 axis [ 29 , 51 ]. As TGF- β 1 and IL-13 signaling induces oxidative stress by producing ROS [ 27 , 52 ], we hypothesized that CIN/NRF2-mediated antioxidant activity contributes to the inhibitory action on both TGF- β 1-induced and IL-13-induced POSTN upregulation. As expected, under our experimental conditions, CIN induced the cytoplasmic-to-nuclear translocation of NRF2 and the NRF2 activation upregulated the expression of HMOX1 and NQO1 at the mRNA level, but only the expression of HMOX1 at the protein level ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CIN is also known to be a potent antioxidant phytochemical that activates the antioxidant NRF2/HMOX1 and NQO1 axis [ 29 , 51 ]. As TGF- β 1 and IL-13 signaling induces oxidative stress by producing ROS [ 27 , 52 ], we hypothesized that CIN/NRF2-mediated antioxidant activity contributes to the inhibitory action on both TGF- β 1-induced and IL-13-induced POSTN upregulation. As expected, under our experimental conditions, CIN induced the cytoplasmic-to-nuclear translocation of NRF2 and the NRF2 activation upregulated the expression of HMOX1 and NQO1 at the mRNA level, but only the expression of HMOX1 at the protein level ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is a characteristic feature in the pathogenesis of a wide spectrum of diseases, including systemic sclerosis, pulmonary fibrotic disorders, renal fibrotic disease, and liver cirrhosis. Although antifibrotic treatments are currently limited [ 10 18 ], recent studies have demonstrated that the activation of nuclear factor erythroid-derived 2-like 2 (NRF2) ameliorates profibrotic processes in the lung, kidney, liver, heart, intestine, and skin [ 19 27 ]. NRF2 is a master antioxidant transcription factor that upregulates the transcription of various genes encoding antioxidant enzymes such as HMOX1 and NQO1 [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In TNBS-induced colitis model, other investigators demonstrated that the main markers of fibrosis (α-smooth muscle actin, collagen I, TIMP-1, and TGF-β1/Smad signaling) and ROS levels were suppressed by tert -butylhydroquinone (tBHQ), an agonist of Nrf2 [91]. The authors revealed that TNBS-induced intestinal fibrosis was reversed by tBHQ administration through inhibition of the ROS-dependent TGF-β1/Smad pathway [21].…”
Section: Role Of Nrf2 Signaling In Intestinal Inflammation and Fibmentioning
confidence: 99%
“…Understanding the exact role of Nrf2 signaling in the pathophysiology of these diseases could be crucial in developing new effective drugs [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Digestive Diseases and Sciences, Guan et al [7] evaluated the effects of tert-butylhydroquinone (tBHQ) on colorectal fibrosis in mice with 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced chronic colitis. The Nrf2 inducer tBHQ, a widely used antioxidant food additive that induces the expression of Nrf2 and Nrf2-related genes in several organs including mouse intestines, significantly attenuated colorectal inflammation and fibrosis, as shown by reduced expression of myeloperoxidase activity, tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), collagen, and α-smooth muscle actin (α-SMA, a marker of activated myofibroblasts).…”
mentioning
confidence: 99%